Influence of product selection criteria on clothing purchase and post-purchase behaviours: A gender and generational comparison - Gustavo Barrera-Verdugo; Antonio Villarroel-Villarroel (PLoS ONE, 2022)
Purchasing and consumption behaviour is a factor with an important impact on sustainable development. In this regard, the clothing category plays a key role due to the high volume of products that are manufactured in countries with poor environmental and social conditions. While some research has investigated personal, social and cultural conditions that influence these behaviours, little is currently known about the influence of the attributes of sustainable clothing selection on the frequency of sustainable purchase and post-purchase actions in this category. This research seeks to evaluate this effect by comparing the results among genders and age/generation and measuring sustainable consumption using the Young Consumers’ Sustainable Consumption Behaviour method, which has two dimensions: purchase choices and sufficient and frugal consumption. Responses to online surveys of 240 university students in Chile are analysed using descriptive statistics, the Mann-Whitney-Wilcoxon test and ologit regressions. The findings show significant differences between the groups analysed with respect to the influence of attributes for sustainable clothing selection and highlight the negative effect of the search for quality in men and in older people. The evidence highlights the need to inform the population about the characteristics of sustainable clothing that positively affect purchase and post-purchase actions such as buying secondhand clothing, repairing, exchanging and donating clothing. This study also suggests that it is important to strengthen the relationship between sustainability and clothing quality among older generations and men.